EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Karlina Karlina; Fitrah Amelia (Universitas Riau Kepulauan, 2019)
This research aims to determine the Effectiveness of the Cooperative Learning Model Snowball Throwing Type on students' mathematics learning outcomes. This type of research is a research experiment with research design One-Group Pretest-Posttest Design. The population of this study was XI SMKIT DBS 01 Batam Academic Year 2018/2019. The sampling technique is done by saturating sampling techniques with many students 19 students. The type of test given is a descriptive test consisting of 8 pretest questions and 8 posttest questions which then analyze the instrument using construct validity and reliability so that 8 valid and reliable questions are obtained with reliable values of pretest